Modified Hasson technique versus Veress technique: a comparative study - George, Robinson; Mathew, Mebin; Radhakrishna, Veerabhadra; Rahman, Ashna; Thenamangalath, Aswini (International Surgery Journal, 2019)
Background: There are two techniques of port placement for laparoscopy, Veress and Hasson. Both have their own advantages of disadvantages. Plenty of new modifications of these techniques have been tried to reduce the risks. We modified Hasson’s technique and evaluated whether the technique is better than the standard Veress technique. Methods: A retrospective analysis was carried out in the Department of General Surgery, Al Azhar Medical College Hospital, India from January 2013 to December 2018. Results: There were 156 patients in group A who underwent laparoscopy by Modified Hasson technique. The Veress technique was used in 149 patients who belonged to group B. There was no difference between the two groups in terms of age and indications for the surgery. The entry time (the time to place the first port) for group A was significantly lesser than that of group B (2.08±0.65 min vs. 4.59±0.53 min; p=0.000). There were a total of two complications in group A which was significantly lesser than that of group B (14; p=0.002). There was no significant difference between the two groups in terms of extraperitoneal port placement, intraperitoneal injury, failure to enter the abdomen, port site seroma, port site infection, port site hematoma, and mortality. But, port site hematoma was significantly lesser in group A compared to group B (0 vs. 5; p=0.027). Conclusions: Modified Hasson’s entry was found to be much better than Veress needle entry due to its simplicity for beginners in laparoscopy, lesser time of achieving pneumoperitoneum and lesser duration of surgery in our study.